Pengaruh Pemberian Makanan Tambahan (PMT) Lokal terhadap Status Gizi Balita Stunting di Desa Wonosari Kecamatan Gadingrejo Kabupaten Pringsewu Tahun 2025: The Effect of Local Supplementary Feeding on the Nutritional Status of Stunted Toddlers at the Wonosari Village of Gadingrejo Sub-District in Pringsewu Regency 2025 - Afriany, Eria; Syafitri Almufaridin , Anissa; Yani Veronika , Septika; Sukarni, Sukarni (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Stunting is one of the global nutritional challenges and problems currently faced by communities worldwide. The impact of stunting is not limited to short stature but also includes impaired intellectual, cognitive, and motor development and may even reduce productivity, leading to economic losses in the future. The World Health Assembly has set an ambitious target to reduce the global prevalence of stunting by 40% by 2025. This research objective is to determine the effect of local supplementary feeding on the nutritional status of stunted toddlers in Wonosari Village, Gadingrejo Sub-district, Pringsewu Regency, in 2025. This study used a quantitative approach with a quasi-experimental research design. The study population consisted of 10 stunted toddlers, selected using a total sampling technique. Data were analyzed using the Wilcoxon Signed-Rank Test to determine the effect of local PMT on the nutritional status of stunted toddlers. The research was conducted in the working area of Wonosari Village, Gadingrejo Sub-district, from September to October 2025. The results showed that the mean z-score of toddlers before the provision of PMT was −2.5530, and after the intervention, it became −2.0960. The Wilcoxon Signed-Rank Test yielded a p-value of 0.415 (p > 0.05), indicating that there was no statistically significant difference in z-scores before and after the provision of local PMT. Nevertheless, the toddlers’ body weight still increased during the intervention period. It is expected that parents will continue to provide balanced, nutritious foods and routinely monitor their children’s growth to achieve optimal improvements in nutritional status.